USE OF CATION-EXCHANGE EQUILIBRIA TO INVESTIGATE THE PARTITIONING OF TUNGSTEN BETWEEN HETEROGENEOUS PHASES OF A FLUID - Kotelnikov A.R.; Musayev A.A.; Averina A.S.; Ganeyev I.G. (My University, 1990)
The phases of a stratified fluid, each concentrating different components of the original mixture, that constituted the initial fluid, may evolve separately in the course of subsequent flow through porous media, in accordance with the properties of each phase and the conditions in the environment. It appears important to determine experimentally the partitioning of ore components among the phases of such a heterogeneous fluid. We have demonstrated that cation exchange equilibria can be used to evaluate the partition coefficients of elements among phases of a stratified fluid. Our preliminary results indicate that the concentration of tungsten is higher in the liquid phase of the fluid (in the H2O-NaCl system) than in the vapor phase.